Hyperoside protects against cerebral ischemia-reperfusion injury by alleviating oxidative stress, inflammation and apoptosis in rats. Issue 1 (1st January 2019) - He, Jinting; Li, Haiqi; Li, Gaofeng; Yang, Le
Abstract: This study investigated the effects of hyperoside pre-treatment on the oxidative stress, inflammatory response and apoptosis in rats with cerebral ischemia-reperfusion (I/R) injury. SD rats were randomly divided into sham, I/R, hyperoside (I/R + Hyp) and nimodipine (I/R + Nim) groups. The rats in the hyperoside group and the nimodipine group were intra-gastrically given hyperoside (50 mg/kg/day) and nimodipine (15 mg/kg/day), respectively, 15 days before operation. A rat cerebral ischemia model was established by suture-occlusion 1 h after the last administration. The thread embolus was removed 2 h after the ischemia for the 24 h reperfusion. The results showed that compared with that in the I/R model group, the neurologic function of the hyperoside group rats was significantly improved and the cerebral infarction volume ratio decreased significantly. The total antioxidant capacity, the activity of superoxide dismutase and glutathione peroxidase in the brain tissue of the hyperoside group rats were significantly higher than those in the I/R model group. The content of malondialdehyde, interleukin-1β and tumour necrosis factor-α in the brain tissue of the hyperoside group rats was significantly lower than that in the I/R model group. Compared with that in the I/R model group, the expression of Bcl-2 mRNA, and p-PI3K and p-AKT proteins in the hyperoside group increased significantly, whereas that of Bax and caspase-3 mRNA decreased significantly. These results suggest that hyperoside had a significant protective effect against cerebral I/R injury in rats, which is related to its inhibiting the oxidative stress, alleviating the inflammatory response and having anti-apoptotic effects.